Representasi Aksi Sosial dalam Konstruksi Ideologi Media Berita Digital Terkait Kebijakan Pemerintah Selama Pandemi - Jafar Lantowa; Rahmatan Idul (Ranah: Jurnal Kajian Bahasa, 2023)
In response to the Covid-19 pandemic, the government issued several policies disseminated through digital news media. However, these policies often become polemic in the community due to the different reporting based on the ideology of the media. The study aims to reveal the ideological construction of digital news media through linguistic representations of social actions in reporting on government policies during the pandemic through the employment of vocabulary and conjunctions. The data consists of digital news headlines on government policies during the pandemic generated through documentation from the three most popular digital media in Indonesia according to the Reuters Institute Digital News Report, namely Detik.com, Kompas.com, and CNN.com. The Critical Discourse concept applied is Theo van Leeuwen's social action framework to find the linguistic representation of each social action through the choice of words and conjunctions. Data analysis was carried out in two stages: analysis of the dimensions of social action to find linguistic representations of each social action in news discourse through word selection and conjunctions and ideological mapping which forms the basis of ideological classification of digital news media for every government policy related to handling Covid-19. As a result, it appears that detiknews.com does not agree with the implementation of PPKM, supports the vaccination program, and is neutral in social assistance data disputes between the central and regional governments. Kompas.com also stands in the same position on the issue of PPKM and vaccination. However, regarding the social assistance data dispute between the central and local governments, kompas.com tended to be on the government side. Meanwhile, cnnindonesia.com did not even question the PPKM-PSBB polemic, but emphasized its disapproval of paid vaccinations and sided with the central government in the social assistance data dispute between the central and regional governments. AbstrakSebagai respons terhadap pandemi Covid-19, pemerintah mengeluarkan beberapa kebijakan yang disebarkan melalui media berita digital. Sayangnya, kebijakan-kebijakan tersebut tak jarang menjadi polemik karena pemberitaan yang berbeda berdasarkan ideologi yang dianut media tersebut. Penelitian ini bertujuan mengungkap ideologi media berita digital serta konstruksinya melalui representasi linguistik aksi-aksi sosial dalam pemberitaan kebijakan pemerintah selama pandemi melalui pemanfaatan kosakata dan konjungsi. Data berupa judul berita pada platform digital yang memuat kebijakan pemerintah terkait Covid-19 yang dihasilkan melalui dokumentasi terhadap tiga media digital paling populer di Indonesia menurut Reuters Institute Digital News Report, yakni detik.com, kompas.com, dan cnn.com. Konsep wacana kritis yang diterapkan adalah kerangka aksi sosial Theo van Leeuwen untuk menemukan representasi linguistik setiap aksi sosial melalui pemilihan kata dan konjungsi. Analisis data dilakukan pada dua tahapan: analisis dimensi aksi sosial untuk menemukan representasi linguistik setiap aksi sosial dalam wacana berita melalui pemilihan kata dan konjungsi dan pemetaan ideologi yang menjadi dasar klasifikasi ideologi media berita digital terhadap setiap kebijakan pemerintah terkait penanganan covid-19. Hasilnya menunjukkan bahwa detiknews.com tidak setuju dengan penerapan PPKM, mendukung vaksinasi, dan netral dalam kisruh data bansos pusat-daerah. Kompas.com juga berdiri di posisi yang sama terkait PPKM dan vaksinasi. Namun, terkait kisruh data bansos pusat-daerah, kompas.com cenderung di sisi pemerintah. Sementara itu, cnnindonesia.com bahkan tidak mempermasalahkan polemik PPKM-PSBB, menitikberatkan ketidaksetujuannya pada vaksinasi berbayar, dan berpihak pada pemerintah pusat dalam kisruh data bansos pusat-daerah.